UMP to offer Mandarin, signs pact with firms - UMP, PNC (2018)
KUANTAN, Oct 27 : Universiti Malaysia Pahang (UMP) has signed a Memorandum of Agreement (MoA) with Alliance Steel (M) Sdn Bhd (ASSB) and ATOZ Solution Sdn Bhd in an effort to enhance the skills of their employees in Mandarin.